Systemy zarządzania portfelami sojuszy - potrzeba zmian - Rzońca, Waldemar; Brol, Marian W. (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
In the paper, the attention was paid to the great importance of co-operation alliances in the present day economy on one side and to the inadequate management of firms' alliance portfolios on the other. The lack of comprehensive research work dealing with the problems of alliance portfolio management was also pointed out. Moreover the model of coevolution of alliance portfolio and the organizational development of a firm proposed by Schroeter was shortly characterized as well as the model of the management of alliance portfolio developed by Hoffmann was presented. The attention was paid to the need for the cyclic changes in the alliance portfolio management systems. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 204-211